Alterations of GABAergic Neuron-Associated Extracellular Matrix and Synaptic Responses in Gad1-Heterozygous Mice Subjected to Prenatal Stress - Wang, Tianying; Sinha, Adya Saran; Akita, Tenpei; Yanagawa, Yuchio; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2018)
Exposure to prenatal stress (PS) and mutations in Gad1, which encodes GABA synthesizing enzyme glutamate decarboxylase (GAD) 67, are the primary risk factors for psychiatric disorders associated with abnormalities in parvalbumin (PV)-positive GABAergic interneurons in the medial prefrontal cortex (mPFC). Decreased expression of extracellular matrix (ECM) glycoproteins has also been reported in patients with these disorders, raising the possibility that ECM abnormalities may play a role in their pathogenesis. To elucidate pathophysiological changes in ECM induced by the gene–environment interaction, we examined heterozygous GAD67-GFP knock-in (GAD67+/GFP) mice subjected to PS from embryonic day 15.0 to 17.5. Consistent with our previous study, we confirmed a decrease in the density of PV neurons in the mPFC of postnatal GAD67+/GFP mice with PS, which was concurrent with a decrease in density of PV neurons surrounded by perineuronal nets (PNNs), a specialized ECM important for the maturation, synaptic stabilization and plasticity of PV neurons. Glycosylation of α-dystroglycan (α-DG) and its putative mediator fukutin in the ECM around inhibitory synapses has also been suggested to contribute to disease development. We found that both glycosylated α-DG and the mRNA level of fukutin were reduced in GAD67+/GFP mice with PS. None of these changes were detected in GAD67+/GFP naive mice or wild type (GAD67+/+) mice with PS, suggesting that both PS and reduced Gad1 gene expression are prerequisites for these changes. When assessing the function of interneurons in the mPFC of GAD67+/GFP mice with PS through evoked inhibitory post-synaptic currents (eIPSCs) in layer V pyramidal neurons, we found that the threshold stimulus intensity for eIPSC events was reduced and that the eIPSC amplitude was increased without changes in the paired-pulse ratio. Moreover, the decay rate of eIPSCs was also slowed. In line with eIPSC, spontaneous IPSC (sIPSC) amplitude, frequency and decay tau were altered. Thus, our study suggests that alterations in the ECM mediated by gene–environment interactions might be linked to the enhanced and prolonged GABA action that compensates for the decreased density of PV neurons. This might be one of the causes of the excitatory–inhibitory imbalance in the mPFC of psychiatric patients.